Improving global coastal bathymetry from waves – Introducing scalable processing and post-processing workflows for 100 m resolution grids - Reithmeier, Mona; Laut, Ingo; Gawehn, Matthijs; Kleih, Christoph; Schneider von Deimling, Jens; Hartmann, Knut (The International Hydrographic Review, 2025)
Global bathymetry data is essential for coastal mapping, modeling, and management, especially in insufficiently mapped regions. Ocean surface Wave Kinematics Bathymetry from satellite data provides a solution independent of water clarity, seabed habitats, and seafloor brightness. This study presents a fully automatic, scalable, and globally applicable Wave Kinematics Bathymetry processing workflow at 100 m resolution. Validated across eleven sites, it introduces automatic post-processing that eliminates false positives by up to 80 %, reduces depth errors by an average of 4.6 m and enhances data reliability. Deployed on the AWS cloud platform, this scalable method advances efficient global coastal bathymetry mapping.